2022
DOI: 10.20517/and.2021.10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sleep disruption on protein accumulation in neurodegenerative diseases

Abstract: Abnormal accumulation of disease proteins in the central nervous system is a neuropathological feature in neurodegenerative disorders. Recently, a growing body of evidence has supported a role of disruption of the sleep-wake cycle in disease development, pathological changes and abnormal protein accumulation in neurodegenerative diseases, especially in Alzheimer’s disease and Parkinson’s disease. Sleep deprivation promotes abnormal accumulation of disease proteins. Interestingly, amyloid-β (Aβ) has daily oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…23 Growing evidence has suggested that there is a bidirectional relationship between sleep disturbance and AD. 24 Although cerebellum is often considered as a motor coordinator, more recent studies indicate that it also plays an important role in the regulation of rapid eye movement (REM) sleep, non-rapid eye movement (NREM) sleep, and wakefulness. 25 Cerebellar disorders have been shown to disrupt the structure of the sleep-wake cycles.…”
Section: Sleep Disturbance and Eeg Alterations In Early Admentioning
confidence: 99%
“…23 Growing evidence has suggested that there is a bidirectional relationship between sleep disturbance and AD. 24 Although cerebellum is often considered as a motor coordinator, more recent studies indicate that it also plays an important role in the regulation of rapid eye movement (REM) sleep, non-rapid eye movement (NREM) sleep, and wakefulness. 25 Cerebellar disorders have been shown to disrupt the structure of the sleep-wake cycles.…”
Section: Sleep Disturbance and Eeg Alterations In Early Admentioning
confidence: 99%
“…Alzheimer's disease (AD) is the most common neurodegenerative disease. AD develops slowly in the brain, brain blood vessels, and peripheral tissues and is characterized by age‐associated progressive deterioration of cognitive abilities 1,2 . More than 90% of AD patients appear to be sporadic and generally with a late age of onset, while familial AD cases usually show symptoms before the age of 65 or even earlier, accounting for 2%–5% of AD cases 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Although 5%-10% of PD cases are familial, the majority of cases are sporadic [3,6]. The hallmarks of pathological changes in PD are the loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc) and the deposition of α-synuclein (α-syn) in Lewy bodies (LBs) and neurites (LNs) that are widely distributed in the brains of PD cases [6][7][8][9]. The LBs are composed of phosphorylated α-syn (S129), ubiquitinated proteins, and other damaged organelle components [10][11][12].…”
Section: Introductionmentioning
confidence: 99%